Inventio Strategies In Caliph Ali Bin Abi Talib's Selected Speeches - Ahmad, Qutren Nada (2005)
This thesis analysed the rhetorical strategies of Caliph Ali bin Abi Talib through his selected speeches in Nahjul Balaghu, the most authentic compilation of Caliph Ali Bin Abi Talib's speeches. The research questions were designed to investigate the invention of Caliph Ali Bin Abi Talib, within the Classical Canons of Rhetoric. The present study concerned on the extent and the pattern of the usage of logos, the usage pathos and the usage of ethos. However, the analysis of the usage of parhos was limited to the elements of arousing fear only. A total of 75 speeches compiled in the English translation of Nahjul Balagha were content analysed. Each speech was coded for types of logos used (analogy, irony, divine testimony, peer testimony, factual illustration, hypothetical illustration, specific instance, maxim, oath, supernatural), for types of fear appeal used (death, loss of possessions. difficulties, other elements of arousing fear) and for types of ethos used (practical wisdom. moral virtue, trustworthiness. goodwill). Findings showed Caliph Ali Bin Abi Talib used all kinds of rhetorical invention in his speeches. The most popular strategy used by Caliph Ali Bin Abi Talib was practical wisdom, followed by analogy, maxim, factual illustration and hypothetical illustration. But in term of logos, analogy was the most popular proof. Death was the most consistent strategy used in arousing fear, while practical wisdom was commonly used in term of ethos. The findings also revealed that Caliph Ali Bin Abi Talib used different invention on different issue of the speech. Overall, Caliph Ali Bin Abi Talib's rhetorical strategies are in agreement with the Aristotle's rhetoric.